PEMANFAATAN MEDIA PEMBELAJARAN DALAM UPAYA PENINGKATAN HASIL BELAJAR MAHASISWA - Cut Aswar (UIN AR-RANIRY, 2015)
Existing interest that a person against an object is reflected in the behavior. Basically interest is motivated by a person's attention to a particular object of interest, such as attention, curiosity is high, and the need for decisive in selecting the objects to something. Thus, it can be confirmed that a person's interest depends on the attention, curiosity, needs and selection to choose his favorite activities. Interest that is an element in achieving success for someone. If someone is interested in a course, all the attention, curiosity, and the need for a course will be higher, so the higher the learning outcomes achieved on a course that followed. The existence turns impact student interest in learning that has a positive influence on the achievement of learning outcomes of a course. The higher the interest of learners in learning a subject, the higher the learning outcomes of a course he achieved. Conversely the lower the student's interest in learning a subject, then the lower the learning outcomes of a course that achieves.